Peran Gakkumdu dalam Penanganan Tindak Pidana Pemilu 2024 (Studi di Bawaslu Kota Bukittinggi) - Raisa, Muhammad Dhafa; Munandar, Syaiful (Universitas Pahlawan Tuanku Tambusai, 2024)
General elections are a fundamental democratic mechanism in the transfer of power to lead a country. The general election process is still considered the most effective way to achieve the goal of a constitutional transfer of power. The purpose of this research is to examine the role of Gakkumdu, which consists of Bawaslu, the Police and the Prosecutor's Office, in handling election crimes, to find out the obstacles faced by Balai Gakkumdu in handling election crimes, and the efforts made. by Balai Gakkumdu in handling election crimes. This research uses an empirical approach which is useful for providing data and information regarding the role of Gakkumdu in handling election crimes. This research will analyze data by comprehensively understanding the role of Gakkumdu in handling election crimes. From the research results, it can be concluded that elections are often characterized by actions that deviate from democratic principles and various obstacles in the practice of democratic elections themselves, apart from that because the central role of gakkumdu has not been running optimally. It is hoped that this research will find new laws regarding the role of gakumdu in dealing with election crimes that often occur. It is hoped that the results of this research can contribute to the development of science and the development of more comprehensive theories in the future.